2016
DOI: 10.1186/s12979-016-0074-z
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of biomarkers in stroke

Abstract: BackgroundIschemic injury triggers inflammatory cascades and changes in the protein synthesis, neurotransmitters and neuro-hormones in the brain parenchyma that may further amplify the tissue damage. The “Triage® Stroke Panel”, a biochemical multimarker assay, detects Brain Natriuretic Peptide (BNP), D-Dimers (DD), Matrix-Metalloproteinase-9 (MMP-9), and S100β protein generating a Multimarker index of these values (MMX). The aims of this prospective study in consecutive patients with ischemic or hemorrhagic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Instant biomarkers with desirable prognostic values can be of great help in distinguishing patients most likely to benefit from, or be harmed by, a particular therapy, including IV thrombolysis in AIS patients. In this regard, many blood biomarkers have been investigated, with proven potential in stroke diagnosis and recovery . Multiple studies have demonstrated changes in a number of blood biomarkers, such as N‐terminal prohormone of brain natriuretic peptide (NT‐proBNP), copeptin, matrix metalloproteinase‐9 (MMP‐9), and S100 β, are all independently associated with various clinical outcomes .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Instant biomarkers with desirable prognostic values can be of great help in distinguishing patients most likely to benefit from, or be harmed by, a particular therapy, including IV thrombolysis in AIS patients. In this regard, many blood biomarkers have been investigated, with proven potential in stroke diagnosis and recovery . Multiple studies have demonstrated changes in a number of blood biomarkers, such as N‐terminal prohormone of brain natriuretic peptide (NT‐proBNP), copeptin, matrix metalloproteinase‐9 (MMP‐9), and S100 β, are all independently associated with various clinical outcomes .…”
Section: Discussionmentioning
confidence: 99%
“…A very recent study showed an externally validated copeptin‐based risk score is strongly associated with several unfavorable outcomes, including death . Moreover, a panel of multiple biomarkers consisting of BNP, d ‐dimers, MMP‐9, and S100 β protein was also shown to be valuable in detecting increased mortality after stroke . Unfortunately, to date, no blood biomarker in the field of stroke has been unequivocally considered as a validated surrogate marker, which can substitute for a clinical evaluation .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accurate prognosis concerning the outcome can help to plan the rehabilitation process and determine the need for care of caregivers. Many factors including demographic features, clinical scales and biochemical parameters have been assessed until the present according to their usefulness as predictors [1,2,3].…”
Section: Introductionmentioning
confidence: 99%